Infectious Agents and Cancer - Buonaguro, Franco M.; Mbulaiteye, Sam M.; Tornesello, Maria Lina
Infectious Agents and Cancer is an open access, peer-reviewed online journal that encompasses all aspects of basic, clinical, epidemiological and translational research providing an insight into the association between chronic infections and cancer. The journal welcomes submissions in the pathogen-related cancer areas and other related topics, in particular: • HPV and anogenital cancers, as well as head and neck cancers; • EBV and Burkitt lymphoma; • HCV/HBV and hepatocellular carcinoma as well as lymphoproliferative diseases; • HHV8 and Kaposi sarcoma; • HTLV and leukemia; • Cancers in Low- and Middle-income countries. The link between infection and cancer has become well established over the past 50 years, and infection-associated cancer contribute up to 16% of cancers in developed countries and 33% in less developed countries. Preventive vaccines have been developed for only two cancer-causing viruses, highlighting both the opportunity to prevent infection-associated cancers by vaccination and the gaps that remain before vaccines can be developed for other cancer-causing agents. These gaps are due to incomplete understanding of the basic biology, natural history, epidemiology of many of the pathogens that cause cancer, the mechanisms they exploit to cause cancer, and how to interrupt progression to cancer in human populations. Early diagnosis or identification of lesions at high risk of progression represent the current most critical research area of the field supported by recent advances in genomics and proteomics technologies. Moreover “omics” is contributing to and accelerating the discovery not only of novel pathogens, but of genetic predisposition as the genetic make-up of organisms and individuals is unraveled. The hunt for molecular signatures of cancer causation, early cancer, or cancer Achilles heels promises new ways to practice precision medicine and public health. The explosion of knowledge in tumor genomics, tumor biology, targeted therapies, gene-environment interactions, immunology and immunotherapy needs a space for robust and vigorous debate. Infectious Agents and Cancer covers all these areas of biomedical research and any other topics pertinent to the development of preventive strategies, innovative diagnostic and biomolecular methodologies, promising therapeutic strategies for chronic infections and cancer. Immunotherapeutic strategies will include: profiling and activation of dendritic cells; reactivation of the immune system; breaking immune tolerance; modulation of the immune system by cytokines and drug delivery systems.